Relationship between race and outcome in Asian, Black and Caucasian patients with spontaneous intracerebral haemorrhage: data from the Virtual International Stroke Trials Archive (VISTA) and Efficacy of Nitric Oxide in Stroke trial (ENOS) - Krishnan, Kailash; Beishon, Lucy; Berge, Eivind; Christensen, Hanne; Dineen, Robert A.; Ozturk, Serefnur; Sprigg, Nikola; Wardlow, Joanna M.; Bath, Philip M.W. (Wiley, 2018)
Background and purpose: Although poor prognosis after intracerebral haemorrhage relates to risk factors and haematoma characteristics, there is limited evidence for the effect of race-ethnicity. Methods: Data from 1011 patients with intracerebral haemorrhage enrolled into hyperacute trials and randomised to control were obtained from the Virtual International Stroke Trials Archive (VISTA) and Efficacy of Nitric Oxide in Stroke (ENOS) Trial. Clinical characteristics and functional outcome were compared among three racial groups – Asians, Blacks and Caucasians. Results: The majority of patients were Caucasian (78.1%) followed by Asians (14.5%) and Blacks (5.5%). At baseline, Caucasians were older and had larger haematoma volumes; Blacks had lower Glasgow Coma Scale and higher systolic blood pressure (all p<0.05). Although the primary outcome of modified Rankin scale (mRS) did not differ at 90 days (p=0.14), there were significant differences in mortality (p<0.0001) and quality of life (EQ-5D p<0.0001; EQ-VAS p 0.015). In test of multiple comparisons, Caucasians were more likely to die (p=0.0003) and had worse quality of life (EQ-5D p=0.003; EQ-VAS p<0.0001) as compared to Asians. Conclusion: Race-ethnicity appears to explain some of the variation in clinical characteristics and outcomes after acute intracerebral haemorrhage. Factors that explain this variation need to be identified.